Environmental protection in Islamic jurisprudence and the Saudi law - Badran, Dr. Duaa Mohammed Ibrahim (The journal of contemporary issues in business and government, 2021)
The environment and its components are considered the vital environment in which humans live .Environment has become the concern of society as a whole .In addition, the goal of providing a safe environment for humans’ livelihood has become one of the priorities of countries at the global and domestic and national levels on equal basis. Every country undertakes the appropriate measures which preserve the environment in its region and enact the necessary legislations to achieve this purpose as well. The various state agencies are considered the bodies responsible for protecting the environment in their region. The administrative authorities, for example, have the powers granted by the law to preserve the environment and deter violations. Such measures are nothing but implementation of the teachings of the true religion (Islam) and its intact rules that dealt with this crucial issue in accordance with a number of long-standing jurisprudential rules which the work of the administrative control authorities does not deviate from its content during the implementation of the environmental protection in the state. The administrative control authorities play an effective role in achieving the goal of protecting the environment. Through conducting this study, we show the means of administrative control in protecting the environment according to the Islamic Sharia and the enforce law.